Pengaruh Komunikasi Persuasif Influencer Fadil Jaidi terhadap Minat Beli Produk Scarlett Whitening - Putri, Alya Saniyyah; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (Jurnal Pustaka Komunikasi, 2024)
The use of influencers has become widespread among companies or business entities to promote their products and services. Influencers are required to convey persuasive messages through endorsement content to increase purchase intention among the public. This research aims to measure the extent of the influence of Fadil Jaidi's persuasive communication on the purchasing intention in Scarlett Whitening products among Instagram followers @fadiljaidi. This research uses the Elaboration Likelihood Theory to determine which route followers @fadiljaidi take in processing the persuasive messages. Researchers use a quantitative approach with correlation research type and positivism paradigm. The data is collected through online questionnaires distributed to 400 respondents Instagram followers @fadiljaidi. Data analysis techniques include t-test hypothesis, simple linear regression test, and coefficient of determination test. The results show that Fadil Jaidi as a male non-beauty influencer has succeeded in carrying out persuasive communication of the Scarlett Whitening product as a beauty product to his followers on Instagram @fadiljaidi. Influencer Fadil Jaidi's persuasive communication has a high influence on purchase intention Scarlett Whitening products, as evidenced by respondents being more influenced through the central route than the peripheral route when processing the persuasive message conveyed by Fadil Jaidi.